A system of development technology and its applications in the Third World - H. A. Havemann (Intereconomics, 1980)
Development technology will have a crucial role to play in the realization of the Third World's ambitious industrialization plans. Professor Havemann presents a system of development technologies which is expected to help in establishing appropriate organizational and research facilities.
Keywords: 330; Technology